(untitled) (TAJ: Journal of Teachers Association, 2009)
The study was carried out with an aim to make a correlation between radionuclide renography and biochemical test in the evaluation of renal diseases. A total of 275 patients with a history of low back pain were included in the study. Radionuclide renography and biochemical test were done in most of them in consecutive days. Among them, 241 patients were finally found to be positive. Available USG, X-ray, IVU, TC, DC, ESR and Hb% findings were also correlated well with renogram. Renal diseases like renal stone, acute glomerulonephritis (AGN), ureteric stone, enal abscess, chronic renal failure, end stage renal disease (ESRD) and renal trauma were ound in most of the cases. In case of radionuclide renography, mild to severe renal nsufficiency found in 87.64% cases (single & bilateral) in contrast to biochemical test where ncreased blood urea/ serum creatinine found in 30.91% cases. Our study focuses the mportance of renogram technique over biochemical test for precise evaluation of differential renal function. doi: 10.3329/taj.v16i2.3885 TAJ December 2003; Vol.16(2): 65-67